Does the use of intraoperative measurement reduce limb length discrepancies after total hip arthroplasty? - Junzhe Wu; Xunrong Zhuang; Chaohui Lin; Lijiang He; Rongmou Zhang (BMC Musculoskeletal Disorders, 2023)
Abstract Purpose Postoperative limb length discrepancy (LLD) is a common complication of total hip arthroplasty, and several methods exist to prevent LLD, but each has its benefits and drawbacks. The study investigates the application of intraoperative lower limb length measurement in preventing postoperative LLD. Methods This study retrospectively analyzed 70 patients who underwent total hip arthroplasty from October 2018 to July 2022. The length of the lower limb on the operated side was measured intraoperatively using a sterilized paper ruler after the fitting of the trial mould and compared with the healthy side. Then the prosthesis size, depth and neck length were adjusted accordingly. Results The absolute value of postoperative LLD was found to be 6.68 ± 4.48 mm, of which 53 cases (75.7%) were less than or equal to 10 mm, while 30 patients (42.9%) were less than or equal to 5 mm. Conclusion The use of intraoperative measurement is effective in reducing LLD after total hip arthroplasty.